2015
DOI: 10.1007/s00134-015-3845-7
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous IgG hypogammaglobulinaemia in critically ill adults with sepsis: systematic review and meta-analysis

Abstract: This systematic review identifies studies of limited quality reporting heterogeneous sepsis cohorts with varying lower limits of normal for IgG. Although our data suggest that a subnormal IgG measurement on the day of sepsis diagnosis does not identify a subgroup of patients with a higher risk of death, further studies are needed to confirm or refute this finding, and whether optimal cut-offs and time windows can be defined for IgG measurement. This would determine whether patients receiving intravenous immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 33 publications
2
57
1
2
Order By: Relevance
“…Nonetheless, the impact of endogenous immunoglobulins levels on the risk of mortality in sepsis remains a controversial issue. A recent meta-analysis leaded by Shankar-Hari M found that the prevalence of IgG hypogammaglobulinemia on the day of sepsis diagnosis is as high as 70%, but this finding did not identify a subgroup of patients with a higher risk of death [2]. Recently, results from the SBITs (Score-based immunoglobulin G therapy of patients with sepsis) study showed that initial low IgG levels did not discriminate between survival and non-survival in patients with severe sepsis and septic shock [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the impact of endogenous immunoglobulins levels on the risk of mortality in sepsis remains a controversial issue. A recent meta-analysis leaded by Shankar-Hari M found that the prevalence of IgG hypogammaglobulinemia on the day of sepsis diagnosis is as high as 70%, but this finding did not identify a subgroup of patients with a higher risk of death [2]. Recently, results from the SBITs (Score-based immunoglobulin G therapy of patients with sepsis) study showed that initial low IgG levels did not discriminate between survival and non-survival in patients with severe sepsis and septic shock [3].…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of factors that in our opinion have not been appropriately addressed in the studies evaluating the predictive ability of immunoglobulins: (1) we have demonstrated in a recent article that disease severity strongly influences biomarker performance in sepsis [6]; (2) the influence of previous immunosuppression has not been evaluated [5]; (3) the impact of immunoglobulins on hospital mortality has not been sufficiently studied, with the majority of works being focused on the acute period of the disease [2]; (4) finally, the ability of endogenous immunoglobulin levels to predict mortality in patients fulfilling the SEPSIS-3 criteria [7, 8] has not been reported to the present moment.…”
Section: Introductionmentioning
confidence: 99%
“…For example, intravenous immunoglobulin (IVIg) trials test effects of immunomodulation and normalisation of low immunoglobulin levels in sepsis, with no consistent benefits [31]. However, enriching on low immunoglobulins alone may not overcome this [32], but enriching a sepsis population with combination of low immunoglobulin levels alongside raised free light chains implying impaired immunoglobulin production, might [33]. Prognostic enrichment, which uses the risk of the study outcome as predicted by baseline covariates, relies on the observation that treatment effects usually exert a fixed relative risk of benefit regardless of the individual patient's risk of the outcome.…”
Section: Discussionmentioning
confidence: 99%
“…There is no doubt that sepsis leads to a significant dysfunction of the immune system; however, the evaluation of immune dysfunction is not a common clinical practice. There are few clinical sites where immunoglobulin concentrations are measured despite the fact that significant hypogammaglobulinemia could be a risk factor for increased mortality in critically ill patients (Shankar-Hari et al 2015). Increased mortality was observed in immunoparalysis condition which can be recognized using relatively simple methods.…”
Section: Immune System Monitoring-when a Little Can Mean A Lotmentioning
confidence: 99%